Evaluation of knowledge and awareness of diabetes in higher secondary level students of Kaski district: A cross-sectional study - Arpana Pandit; Biswash Sapkota; Nishan Poudel; Renu Karki; Bharat Poudel; Ramakanta Lamichhane (PLoS ONE, 2025)
Studies have shown that the knowledge of diabetes among adults in Nepal is poor. This study aimed to evaluate the knowledge regarding diabetes in secondary level (i.e., Grade 11 and 12) science students. We assessed the student’s knowledge and awareness regarding diabetes through self-administered questionnaires consisting of 26 questions associated with symptoms, treatment, prevention, and complications of diabetes. Eight higher secondary schools with science streams in Kaski district were selected. A total of 561 students were in the study. Almost all the students (96%) expressed that they had heard about diabetes but only 37% of students correctly indicated the risk factors of it. One-fourth of the total students were able to distinguish between type 1 and type 2 diabetes. Only 13% of students knew about the third type of diabetes, i.e., gestational diabetes. Nearly 47% of students had a wrong perception that diabetes cannot be prevented or delayed. Though early diagnosis of diabetes is essential to prevent complications, only 61% knew about this fact. In our study, 26% of respondents had a family history of diabetes. Overall, 53% showed poor knowledge, 44% showed average knowledge and only 3% showed good knowledge regarding diabetes. The study showed that the gender of the participants and the type of college (government or private) they were studying had no significant relationship with the knowledge level regarding diabetes. However, family history and educational level (class 11 or 12) showed a positive relationship with the level of knowledge regarding diabetes. Students had good knowledge regarding the symptoms of diabetes but had poor knowledge about risk factors, complications, and prevention strategies for diabetes. Overall diabetes knowledge was inadequate in the students, indicating that there is a necessity for urgent action to enhance students’ knowledge regarding diabetes.